Respons Pertumbuhan dan Hasil Sawi Pagoda (Brassica narinosa L.) Akibat Pemberian Arang Tempurung Kelapa dan Pupuk Nitrogen pada Tanah Podsolik Merah Kuning - Alifia, Wina Rizky; Wasi'an, Wasi'an; Ramadhan, Tris Haris (Perkebunan dan Lahan Tropika, 2025)
Agriculture in Indonesia has various types of crop commodities that can be cultivated and developed for food, clothing, and medicinal needs. One such crop is pagoda mustard (Brassica narinosa L.). This study aims to determine the effect of the interaction and optimal dosages of coconut shell charcoal and nitrogen fertilizer on the growth and yield of pagoda mustard in yellow-red podzolic soil. The research was conducted in the Greenhouse of the Faculty of Agriculture, Tanjungpura University, Pontianak, from July, 2024, to September, 2024. This study employed a factorial completely randomized design (CRD) with two factors. The first factor being coconut shell charcoal (K) with two levels, and the second factor being nitrogen fertilizer (N) with three levels, each replicated four times. The first treatment factor consisted of coconut shell charcoal at two levels: 40 g/polybag and 80 g/polybag. The second treatment factor involved nitrogen application at three levels: 2.25 g/plant, 2.8 g/plant, and 3.3 g/plant. In total, there were six treatment combinations, each replicated four times, resulting in 24 experimental units. Each experimental unit contained five sample plants, leading to a total of 120 plants. The observed variables included leaf count, root volume, dry weight of the plants, and fresh weight of the plants. The results indicated an interaction between the application of coconut shell charcoal and nitrogen fertilizer on the dry weight and root volume variables. The use of 80 g/plant coconut shell charcoal combined with 3.30 g/plant nitrogen fertilizer produced the best growth and yield for pagoda mustard in yellow-red podsolic soil.